Indonesia - Avoiding the Trap : Development Policy Review 2014 - World Bank (Washington, DC, 2014)
Within the next two decades Indonesia aspires to generate prosperity, avoid a middle-income trap, and leave no one behind as it tries to catch up with high-income economies. Can Indonesia achieve them? This report argues that the country has the potential to rise and become more prosperous and equitable. But the risk of floating in the middle is real. Which pathway the economy will take depends on: (i) the adoption of a growth strategy that unleashes the productivity potential of the economy; and (ii) consistent implementation of a few, long-standing, high-priority structural reforms to boost growth and share prosperity more widely. Indonesia is fortunate to have options in financing these reforms without threatening its long-term fiscal outlook. The difficulties lie in getting the reforms implemented in a complex institutional and decentralized framework. The report identifies the reforms of institutions and processes that govern the functioning of the state as critical for unleashing the country's development potential. The report provides an analytical underpinning for the Bank's country partnership strategy 2009-14 and shapes the Bank's support to the government's rencana pembangunan jangka menengah nasional (RPJMN) 2010-2014.